The DAL82 protein of Saccharomyces cerevisiae binds to the DAL upstream induction sequence (UIS). - Dorrington, R A (1993)
Expression of the DAL2, DAL4, DAL7, DUR1,2, and DUR3 genes in S. cerevisiae is induced by allophanate, the last intermediate in the allantoin catabolic pathway. Analysis of the DAL7 promoter identified a dodecanucleotide, the DAL7 UIS, which was required for inducer-responsiveness. Operation of the DAL7 UIS required functional DAL81 and DAL82 gene products. Since the DAL81 product was not an allantoin pathway-specific regulatory factor, the DAL82 product was considered as the more likely candidate to be the DAL UIS binding protein. Using an E. coli expression system, we showed that DAL82 protein specifically bound to wild type but not mutant DAL UIS sequences. DNA fragments containing DAL UIS elements derived from various DAL gene promoters bound DAL82 protein with different affinities which correlate with the degree of inducer-responsiveness the genes displayed.